Soft ethics, the governance of the digital and the General Data Protection Regulation - Floridi, L (Royal Society, 2018)
The article discusses the governance of the digital as the new challenge posed by technological innovation. It then introduces a new distinction between soft ethics, which applies after legal compliance with legislation, such as the General Data Protection Regulation in the European Union, and hard ethics, which precedes and contributes to shape legislation. It concludes by developing an analysis of the role of digital ethics with respect to digital regulation and digital governance.This article is part of the theme issue 'Governing artificial intelligence: ethical, legal, and technical opportunities and challenges'.